Pesticide sensitivity and hypersensitivity - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes pesticide sensitivity and hypersensitivity, lists pesticides which cause hypersensitivity, and outlines how to diagnose and live with hypersensitivity.
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Environmental aspects; Human beings -- Effect of pesticides on; Allergy; Pesticides -- Risk mitigation